PENGARUH MODEL VALUE CLARIFICATION TECHNIQUE (VCT) BERBANTUAN WORDWALL DAN CANVA TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Puteri, Annisa Nurul; Herpratiwi; Hariyanto; Nurwahidin, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low learning outcomes of Pancasila education of grade IV students of UPTD SD Negeri 1 Sumber Hadi. This study aims to determine (1) the effect of the application of the VCT learning model assisted by wordwall on the learning outcomes of Pancasila education of grade IV elementary school students (2) the effect of the application of the VCT learning model assisted by canva on the learning outcomes of Pancasila education of grade IV elementary school students (3) the difference in the effect of the application of the VCT learning model assisted by wordwall and canva on the learning outcomes of Pancasila education of grade IV elementary school students. The method used in this study is quantitative with a quasi-experimental design type, namely non-equivalent control group design. The population is 34 students, by determining the research sample using probability sampling techniques in the form of cluster random sampling. Data collection techniques in this study use tests and non-tests. Hypothesis testing uses paired sample t-test and independent sample t-test. The results of the study (1) there is an influence of the application of the VCT learning model assisted by wordwall on the learning outcomes of Pancasila education with a significance of 0.000 (2) there is an influence of the application of the VCT learning model assisted by canva on the learning outcomes of Pancasila education with a significance of 0.000 (3) there is a difference in the influence of the application of the VCT learning model assisted by wordwall and canva on the learning outcomes of Pancasila education with a significance of 0.045.